NF-κB-inducing kinase activates IKK-α by phosphorylation of Ser-176 - Ling, Lei (The National Academy of Sciences, 1998)
Activation of the transcription factor NF-κB by inflammatory cytokines involves the successive action of NF-κB-inducing kinase (NIK) and two IκB kinases, IKK-α and IKK-β. Here we show that NIK preferentially phosphorylates IKK-α over IKK-β, leading to the activation of IKK-α kinase activity. This phosphorylation of IKK-α occurs specifically on Ser-176 in the activation loop between kinase subdomains VII and VIII. A mutant form of IKK-α containing alanine at residue 176 cannot be phosphorylated or activated by NIK and acts as a dominant negative inhibitor of interleukin 1- and tumor necrosis factor-induced NF-κB activation. Conversely, a mutant form of IKK-α containing glutamic acid at residue 176 is constitutively active. Thus, the phosphorylation of IKK-α on Ser-176 by NIK may be required for cytokine-mediated NF-κB activation.